2022
DOI: 10.1002/rnc.6365
|View full text |Cite
|
Sign up to set email alerts
|

Robust tracking control with reinforcement learning for nonlinear‐constrained systems

Abstract: This article considers the robust tracking control problem of uncertain nonlinear systems with asymmetric input constraints. Initially, the tracking error dynamics and the desired trajectory dynamics are constructed as an augmented system. Then, with a discounted value function being introduced for the nominal augmented system, the original tracking control problem is transformed into a constrained optimal control problem. To solve the constrained optimal control problem, its related Hamilton–Jacobi–Bellman eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Due to accounting for safety constraints and asymmetric input constraints in ( 7 ), the optimal control law does not converge to zero while the system state achieves the stable phase [ 43 ]. The discount factor , may be unbounded, so it is necessary to consider the discount factor.…”
Section: Preliminariesmentioning
confidence: 99%
“…Due to accounting for safety constraints and asymmetric input constraints in ( 7 ), the optimal control law does not converge to zero while the system state achieves the stable phase [ 43 ]. The discount factor , may be unbounded, so it is necessary to consider the discount factor.…”
Section: Preliminariesmentioning
confidence: 99%
“…3 However, the HJB equation of nonlinear systems is a nonlinear partial differential equation, and its analytical solution is difficult or even impossible to obtain. [4][5][6] Therefore, how to solve the HJB equation becomes the first challenge to be faced. Adaptive dynamic programming (ADP) using neural network (NN) approximation techniques is a powerful method for solving the HJB equation in optimization problems, [7][8][9] and many ADP-based methods [10][11][12] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Solving the optimal control problem is mainly to solve the Hamilton–Jacobi–Bellman (HJB) equation 3 . However, the HJB equation of nonlinear systems is a nonlinear partial differential equation, and its analytical solution is difficult or even impossible to obtain 4‐6 . Therefore, how to solve the HJB equation becomes the first challenge to be faced.…”
Section: Introductionmentioning
confidence: 99%
“…If ignoring saturation during the design of controllers, the systems' performance often becomes awful and unacceptable. 14 Abu-Khalaf and Lewis 15 first introduced an off-line RL approach to solve the optimal control problem of continuous-time saturated nonlinear systems. After that, Luo et al 16 suggested an off-policy RL algorithm to derive the optimal control of discrete-time saturated nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…Many actuators are often subject to saturation because of physical restrictions, such as temperature and pressure. If ignoring saturation during the design of controllers, the systems' performance often becomes awful and unacceptable 14 . Abu‐Khalaf and Lewis 15 first introduced an off‐line RL approach to solve the optimal control problem of continuous‐time saturated nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%